Rancang Bangun Sistem Informasi Tempat Pemakamam Umum Pondok Rajeg Bogor Berbasis Web - Ibnu Rusdi; Indra Febria Widy; Hisyam Husein (JURNAL TEKNIK KOMPUTER, 2019)
The use of information technology has a very broad scope. One of them is in the field of funeral. Funeral is often a "backward" issue in this life. Even if we look at our "nature" as human beings, we will all experience what is called death. The thing we need to prepare for death besides worship is that we need to prepare our final rest right. We often forget this, even though if we see the phenomenon that the world mortality rate is increasing every day, even Indonesia is one of the countries with a very high mortality rate. The high mortality rate is not in line with the number of locations or burial places available. This has become a problem that must be solved and become a problem that is quite serious and needs serious handling. One of the solutions to this problem is the use of information technology to record the overall mortality rate and also record the availability of existing locations to bury it. That way the government can monitor every problem that exists and can provide solutions that can be disseminated easily by utilizing information technology, the author uses the Waterfall method to facilitate the process of needs analysis until testing the design of building information systems public cemetery (TPU) Pondok Rajeg Bogor.